Territories of Washington and Oregon by Prof. H.D. Rogers & A. Keith Johnston F.R.S.E. - Rogers, H.D. (Cartographer); Johnston, A. Keith (Contributor)
Topographical map of Western North America, including territories of British America, Nebraska, Washington, Oregon, and California. Oregon and Washington cover present day Idaho and Montana. Coloured markings show lines of municipal territories and a proposed railway. Scale approximately 1:3,450,000 or 54.5 miles to 1 inch. Relief shown by hachures. Originally published in : Atlas of the United States of North America : Canada, New Brunswick, Nova Scotia, Newfoundland, Mexico, Central America, Cuba, and Jamaica. London : John Murray, 1857 Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .